Upaya Meningkatan Prestasi Belajar Siswa dengan Metode Make A Match pada Mata Pelajaran Ilmu Pengetahuan Sosial di Kelas IX-C SMP Negeri 4 Praya - Edi Supardi (Universitas Pendidikan Mandalika (UNDIKMA), 2019)
The purpose of this research was to improve the students learning achievement of Social Sciences (IPS) in class IX-C of SMP Negeri 4 Praya by using Make A-Match learning method. This research used classroom action research methods and was carried out at the fourth class of IX-C in the even semester of the academic year 2018/2019 with 39 students, in which 16 male students and 23 female students. The sequence of research activities included: (1) Planning, (2) Implementation of actions, (3) Observation, (4) Reflection. The result of the study showed that Make-a Match method was proven to improve the students learning achievement as seen in the result of recapitulation of each cycle from the first cycle, in which 26 students or 65% were said to be complete and 13 students or 33% were not complete, and in the second cycle 37 students or 92.31% were said to be complete and 3 students or 7.69% had not been complete. From the recapitulation result of each cycle above, it was seen that cycle I to cycle II increased by 4.57%. Thus, it can be concluded that the use of Make-a Match learning method can improve the students learning achievement of Social Sciences (IPS) in class IX-C of SMP Negeri 4 Praya in the year of 2018/2019.